Miss Julia rocks the cradle - Ross, Ann B. (Waterville, Me. : Thorndike Press, 2011)
Miss Julia's investigative work on a possible murder and her financial reputation keeps her buzzing. But the sudden arrival of Hazel Marie's twins during a fierce blizzard brings a whole new set of challenges and a double helping of trouble.
Keywords: Springer, Julia (Fictitious character); City and town life -- North Carolina; Twins; Large type books; Humorous fiction